PERANAN LAYANAN PERPUSTAKAAN TERHADAP PRESTASI MAHASISWA DI UNIVERSITAS MUHAMMADIYAH SURAKARTA - Nisa, Maria Husnun; Abdilah, Anisa Russitawati; Azny, Masyrifah Ayu; Hidayat, Mansur (FPPTI Jawa Tengah, 2020)
The Library of the Muhammadiyah University of Surakarta (UMS) is a center for academic activities based on information technology and has been accredited “A”. The main product of the library is a service. Service is the spearhead of the library because it is directly related to users. This study aims to determine the role of (1) service; (2) infrastructure / facil- ities and (3) library collections / information on student achievement index. The research method used is the quantity method using the product moment statistical test (Pearson correlation). The results showed that (1) UMS library service was good according to most respondents but there was no relationship between library services and student achievement index because t count was less than t table (0.250 <0.279); (2) respondents stated that the infrastructure / facilities and infrastructure of the UMS library were in accordance with the expectations of students, but there was no significant relationship between infrastructure / facilities and infrastructure with the student achievement index because t count <t table (0.106 <0.279); (3) there is a significant relationship between the collection / information of the UMS library on the student achievement index where t (0.307)> t table (0.279).